Psychological consequences of intra-familial violence in adolescents - Τζαμαλούκα Γ.; Ζύγα Ε.; Φωτεινέα Ε.; Παπαδακάκη Μ.; Χλιαουτάκης Ι. (Psychology: the Journal of the Hellenic Psychological Society, 2020)
The abstract is available in the PDF